A Novel Image Analysis of Light Emitting Diode Array Biostimulation Applied on Microcirculation - Su, Chuan-Tsung; Shan, Yi-Chia; Fang, Wei; Lin, Chii-Wann; Juan, Ju-Hsuan; Lu, Kuan-Ting; Wu, Jih-Huah (2018 1st International Cognitive Cities Conference (IC3), 2018)
A novel development platform of the specific microcirculation analysis was proposed in this study. This study was to observe the effect of the blood microcirculation with LED stimulation. The experiment involved the light emitting diode array (LEDA), the designed control board and the image processing algorithm on the platform. LEDA (six LEDs, wavelength 660 nm, operating frequency 8 - 15 Hz) was used to stimulate the palm of the subject, and then, the microcirculation images were analyzed by the image processing algorithm. The blood velocity on the ring finger was increased after LEDA stimulation, and it was approximately 1.7 times compared with and without the light stimulation. Thus, LEDA stimulation on the palm enhanced the microcirculation. Also, a specific platform of LEDA system with microcirculation measurement was developed in this study.